Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4172/2161-1009.1000135
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Protease Isolated from Different Parts of Choerospondias axillaris (Lapsi)

Abstract: Proteases were isolated from leaf, bark and root of Choerospondias axillaris, locally called Lapsi. Choerospondias axillaris is a dioecous, deciduous fruit bearing plant with multiple daily uses. The protease was extracted with 0.1 M phosphate buffer of pH 7 and then precipitated successively with TCA and ammonium sulfate. The protease from leaf showed maximum activity at pH 9, temperature at 20°C. While, bark protease showed optimum pH 5 and temperature 60°C. In case of root the optimum pH was 10 and the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Li et al, (2016) reported the presence of medicinally important phytochemicals in both the pulp and peel of Lapsi. Besides, Protease: a proteolytic enzyme can be isolated from leaf, bark, root (Upadhyay, Magar and Thapa, 2013) and fruit pulp (Prajapati, Sharma and Agrawal, 2009) of the Lapsi. Thus, it is a potential product for national as well as international market (Paudel et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al, (2016) reported the presence of medicinally important phytochemicals in both the pulp and peel of Lapsi. Besides, Protease: a proteolytic enzyme can be isolated from leaf, bark, root (Upadhyay, Magar and Thapa, 2013) and fruit pulp (Prajapati, Sharma and Agrawal, 2009) of the Lapsi. Thus, it is a potential product for national as well as international market (Paudel et al, 2003).…”
Section: Introductionmentioning
confidence: 99%